Learners' collaborative practical investigation on acceleration due to gravity: a comparison of the effect on their understanding using an online learning environment as opposed to face-to-face interaction - Glanville, Nicolette Angjelika Aidan (My University, 2011)
Moodle, an online course management system, has been introduced into the school where this study was conducted. One of the features on Moodle is a forum that allows groups to chat online, enabling online collaborative group work. Learners used the forum to design a practical investigation to study the effects of various factors on the acceleration of a falling body and analyse the results in order to draw a conclusion. Consequently, this study compares the effects on learners‟ participation within a group and learners‟ understanding of acceleration due to gravity using an online learning environment as opposed to face-to-face interaction. The study also investigates learners‟ perceptions of the use of activities in Moodle as effective learning tools. Alternative conceptions regarding acceleration due to gravity are common and persistent. It was hoped that a peer group collaborative practical investigation may help challenge these alternative conceptions. Time in class for collaborative learning is limited due to a full curriculum and learners have extensive extramural commitments in the afternoons that limit collaborative opportunities. However, our learners have access to the Internet and are familiar with online social networking. Items in the pre-test and post-test were based on the Force and Motion Conceptual Evaluation devised by Thornton and Sokoloff (1998). Contrary to their findings that showed a disappointingly small improvement in the scores after traditional teaching, test scores for learners in this study dropped after completing the practical investigation. Another post-test administered seven weeks later showed that many learners had reverted back to previous alternative conceptions. It is possible that the frameworks learners use to solve textbook problems are replaced with intuitive conceptions when faced with with real life application of the laws in their practical investigation. With regard to the collaborative group work, the findings suggest that while there were far fewer off-task comments on the online forum, less challenging of alternative conceptions occurred, with participants often re-stating the correct conception without engaging with the other participants. The face-to-face contained lively debates and the use of good analogies but there were also cases where the voice of reason was drowned-out by more insistent alternative conceptions. Some learners found the discussion on the forum disjointed and difficult to follow. Aspects of the forum can be changed to minimize these problems in future. Most learners enjoyed the self-marking tests and questionnaires. Overall, neither the collaborative discussions on either the Moodle forum or face-to face, nor the practical investigation helped to challenge alternative conceptions.